A Hybrid Metaheuristic for Multiple Runways Aircraft Landing Problem Based on Bat Algorithm - Jian Xie; Yongquan Zhou; Hongqing Zheng (Journal of Applied Mathematics)
The aircraft landing problem (ALP) is an NP-hard problem; the aim of ALP is to minimize the total cost of landing deviation from predefined target time under the condition of safe landing. In this paper, the multiple runways case of the static ALP is considered and a hybrid metaheuristic based on bat algorithm is presented to solve it. Moreover, four types of landing time assignment strategies are applied to allocate the scheduling time, and a constructed initialization is used to speed up the convergence rate. The computational results show that the proposed algorithm can obtain the high-quality and comparable solutions for instances up to 500 aircrafts, and also it is capable of finding the optimal solutions for many instances in a short time.